Appraising Goat Support for Educational Continuation in Kallery Secondary School, Dhading: Rural/Development Perspective - Pasa, Rajan Binayak; Bishwokarma, Lila Bahadur (Nepalese Journal of Development and Rural Studies, 2022)
This paper has attempted to explore how a small support can make a big difference to cope-with poverty challenges in rural life. It is about an innovative way of support entitled ‘goat support for educational continuation’ for few children of poor families of Galchhi rural municipality, Dhading, provided before a decade (in 2012 and 2013). It applied narrative inquiry research strategy and used a blended mode of data collecting techniques (observation, KII and case study) for appraising lost and benefits of the p[roject. It has exemplified that if we use resources properly and innovatively and act cooperatively, we can make difference. It has exemplified that school and community people can solve some of educational problems while they act cooperatively. It was really a cooperative work and initiatives among school family, parents and helping hands to address problems of poor families. It is because the notion of development has rapidly been changing so that our worldviews and acts on rural/development must be changed according. A simple but become a model approach of sustainable rural development practice.